Lawn boy - Paulsen, Gary. (New York : Wendy Lamb Books, 2007)
Things get out of hand for a twelve-year-old boy when a neighbor convinces him to expand his summer lawn mowing business.
Keywords: Business enterprises -- Juvenile fiction; Summer employment -- Juvenile fiction